Adenovirus pulmonary infections identified by PCR and in situ hybridisation in bone marrow transplant recipients. Issue 11 (November 1994) - Matsuse, T; Matsui, H; Shu, C Y; Nagase, T; Wakabayashi, T; Mori, S; Inoue, S; Fukuchi, Y; Orimo, H
Abstract : AIMS–To investigate adenovirus pulmonary infections in bone marrow transplant (BMT) recipients. METHODS–Formalin fixed, paraffin wax embedded lung tissue was examined from 13 necropsy cases after BMT using PCR and in situ hybridisation to detect adenovirus DNA. The E1A region of the adenoviral genome was targeted for PCR. In situ hybridisation was performed only in the PCR positive cases. RESULTS–Of the 13 lung specimens analysed, nine cases were negative for adenoviral nucleic acid. Four (30%) PCR and two (15%) in situ hybridisation positive cases were found. In some of the patients there were clinical and pathological indications that some diseases might be associated with adenovirus infection–haemorrhagic cystitis (three cases); necrotising pneumonia (one case). In necrotising pneumonia in which no pathogenic agents had been shown by conventional histological study, the in situ hybridisation technique showed positive staining for adenovirus. In a patient who died of renal failure caused by adenovirus nephritis, both PCR and in situ hybridisation were positive in the lung as well as in the kidney, although no histological change was found. Two PCR positive cases lacked positive sites for adenovirus by in situ hybridisation. CONCLUSIONS–The combination of PCR and in situ hybridisation could be useful for diagnosing adenovirus infection of the lung in BMT recipients. These results provide a basis for exploring further the clinical use of PCR and in situ hybridisation to diagnose adenovirus infection.